Primož Trubar in Bartolomé de Las Casas - Pregelj, Barbara (Slavia Centralis, 2020)
Primož Trubar and Bartolomé de Las Casas. Primož Trubar and Bartolomé de Las Casas were contemporaries. It is possible to draw several parallels regarding the life and work of both authors (they both travelled extensively, they caused conflicts due to their activities, their opus is extensive, their genre being semi–literary, and their style is quite similar). But they also differ in many respects. These differences are mainly due to the sense of belonging to two great religious movements of the 16th century and their different attitude regarding the meaning of images.